The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.4314/ajtcam.v13i1.17
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of <i>Dracaena cinnabari</i> resin from Soqotra Island on multi drug resistant human pathogens

Abstract: Background: Few studies showed that Dracaena cinnabari resin, collected from Soqotra Island, Yemen, has antimicrobial activity. This study is the first to investigate antimicrobial activity of the resin on both antibiotic multi-resistant human pathogens and on poly-microbial culture. Material and Methods: Antimicrobial activity of ethanolic extract of Dracaena cinnabari resin from Soqotra Island on multidrug resistant Gram-positive and Gram-negative human ATCC standard pathogens and Ascosphaera apis, the causa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 15 publications
0
3
2
Order By: Relevance
“…Compared to antibacterial activities determined previously [22,23,24], the human pathogenic fungi tested appeared to be more susceptible to the resin extracts than the bacterial stains. Previous studies have reported the antifungal activities of D. cinnabari resin against three other species Candida albicans , Aspergillus flavus , and A. niger [22,23,24].…”
Section: Resultscontrasting
confidence: 71%
See 1 more Smart Citation
“…Compared to antibacterial activities determined previously [22,23,24], the human pathogenic fungi tested appeared to be more susceptible to the resin extracts than the bacterial stains. Previous studies have reported the antifungal activities of D. cinnabari resin against three other species Candida albicans , Aspergillus flavus , and A. niger [22,23,24].…”
Section: Resultscontrasting
confidence: 71%
“…Compared to antibacterial activities determined previously [22,23,24], the human pathogenic fungi tested appeared to be more susceptible to the resin extracts than the bacterial stains. Previous studies have reported the antifungal activities of D. cinnabari resin against three other species Candida albicans , Aspergillus flavus , and A. niger [22,23,24]. Polyphenols including flavonoids, are the main constituents of the D. cinnabari resin [9,10,14] as well as resins obtained from other species of Dracaena genus such as Dracaena cochinchinensis [8,25], Dracaena draco and Dracaena tamaranae [26].…”
Section: Resultscontrasting
confidence: 71%
“…On the contrary, the other two samples presented a greater fraction of Proteobacteria, and few phyla were not observed by culture-based methods, illustrating the importance of NGS. This also led to the fact that these microbes can spread through a variety of channels that penetrate plant tissues [ 44 , 45 ]. Finally, Proteobacteria, Firmicutes, Actinobacteria, Cyanobacteria, and Bacteriodetes were found to colonize citrus plant leaf tissues [ 46 , 47 ], they have been demonstrated to produce useful bioactive chemicals A comparison of bacterial species based on their structure is referred to as beta diversity.…”
Section: Discussionmentioning
confidence: 99%
“…Also, a dichloromethane extract of D. cinnabari resin has been found to have good inhibitory activity against various food-borne pathogens using an agar disc diffusion method [45]. In addition, the antimicrobial activities of different solvent (chloroform, methanol, and benzene) extracts of D. cinnabari resin against Gram-positive bacteria, Gramnegative bacteria, and fungi revealed that these microorganisms have varied sensitivity to the different extracts [46,47]. Similarly, Altwair and Edrah [48] have reported that aqueous and ethanolic extracts of D. cinnabari significantly inhibited the activity of E. coli (13 & 14 mm), P. vulgaris (9 and 10 mm), P. aeruginosa (8 and 9 mm), K. pneumonia (7 and 8 mm), and S. saprophyticus (10 and 11 mm), respectively.…”
Section: Antimicrobial Effectsmentioning
confidence: 99%